2011
DOI: 10.1186/1750-1326-6-36
|View full text |Cite
|
Sign up to set email alerts
|

Lack of a-disintegrin-and-metalloproteinase ADAM10 leads to intracellular accumulation and loss of shedding of the cellular prion protein in vivo

Abstract: BackgroundThe cellular prion protein (PrPC) fulfils several yet not completely understood physiological functions. Apart from these functions, it has the ability to misfold into a pathogenic scrapie form (PrPSc) leading to fatal transmissible spongiform encephalopathies. Proteolytic processing of PrPC generates N- and C-terminal fragments which play crucial roles both in the pathophysiology of prion diseases and in transducing physiological functions of PrPC. A-disintegrin-and-metalloproteinase 10 (ADAM10) has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
105
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(115 citation statements)
references
References 55 publications
9
105
1
Order By: Relevance
“…Taylor et al clearly demonstrated that the ␣-cleavage of PrP C was not affected by the absence of both ADAM10 and ADAM17 in cellulo ). In addition, ADAM10-deficient mice have no alteration in levels of PrPC1 (Altmeppen et al, 2011). Here, we showed that inhibition of ADAM10 and ADAM17 by the general metalloprotease inhibitor marimastat and knockdown of both ADAM10 and ADAM17 expression did not affect the release of PrPN1 in the culture medium under dimerization conditions.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Taylor et al clearly demonstrated that the ␣-cleavage of PrP C was not affected by the absence of both ADAM10 and ADAM17 in cellulo ). In addition, ADAM10-deficient mice have no alteration in levels of PrPC1 (Altmeppen et al, 2011). Here, we showed that inhibition of ADAM10 and ADAM17 by the general metalloprotease inhibitor marimastat and knockdown of both ADAM10 and ADAM17 expression did not affect the release of PrPN1 in the culture medium under dimerization conditions.…”
Section: Discussionmentioning
confidence: 61%
“…More evidence is now challenging the implication of ADAM10 and ADAM17 as the principal ␣-PrPases (Vincent et al, 2001;Laffont-Proust et al, 2005;Taylor et al, 2009;Altmeppen et al, 2011). Taylor et al clearly demonstrated that the ␣-cleavage of PrP C was not affected by the absence of both ADAM10 and ADAM17 in cellulo ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PrP C may be cleaved at its GPI-anchor, allowing shedding of PrP C species from a cell by both protease and phospholipase mediated mechanisms [26][27][28]. PrP C is also subject to two well-described internal cleavage events known as a-and b-cleavage [29].…”
Section: Introductionmentioning
confidence: 99%